2018
DOI: 10.1038/s41598-018-25344-5
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of impacted forest patches less than 5 km2 is a key driver of the incidence of malaria in Amazonian Brazil

Abstract: The precise role that deforestation for agricultural settlements and commercial forest products plays in promoting or inhibiting malaria incidence in Amazonian Brazil is controversial. Using publically available databases, we analyzed temporal malaria incidence (2009–2015) in municipalities of nine Amazonian states in relation to ecologically defined variables: (i) deforestation (rate of forest clearing over time); (ii) degraded forest (degree of human disturbance and openness of forest canopy for logging) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 57 publications
2
85
0
5
Order By: Relevance
“…Similar observations from the Ivory Coast illustrated the impact of land-use modifications on the abundance, distribution, and hostseeking behaviour of Aedes mosquitoes [54]. A study in the Amazon concluded that deforestation is responsible for the increase in malaria incidence [55]. This observation could emphasize the impact of significant deforestation observed across the DRC in relation to the emergence of mosquito-borne viral diseases and repeated outbreaks in the country.…”
Section: Discussionmentioning
confidence: 66%
“…Similar observations from the Ivory Coast illustrated the impact of land-use modifications on the abundance, distribution, and hostseeking behaviour of Aedes mosquitoes [54]. A study in the Amazon concluded that deforestation is responsible for the increase in malaria incidence [55]. This observation could emphasize the impact of significant deforestation observed across the DRC in relation to the emergence of mosquito-borne viral diseases and repeated outbreaks in the country.…”
Section: Discussionmentioning
confidence: 66%
“…Having identified a number of demand-side measures to reduce malaria risk that address the potential role of international trade, it is important to point out that these must be designed with potentially vulnerable smallholders in mind. The commercial trade of basic commodities is a particularly important and reliable source of cash income for smallholders, who exploit natural vegetation, leading to deforestation and malaria 11,[84][85][86] . For instance, charcoal production is closely linked to deforestation in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Their results estimated that a 10% increase in forest area cleared can lead to a 3.3% increase in malaria incidence, and a 1% increase in malaria incidence could decrease 1.4% of forest area cleared. A positive correlation between the number of forest patches affected by deforestation less than 5 km 2 and the incidence of malaria was found in areas across the Brazilian Amazon: each kilometer square of deforestation resulted in 27 new malaria cases 11 . In the westernmost municipality in the Brazilian Amazon, statistical associations between malaria incidence and cumulative percentage of land deforested were found using univariate and multivariate general additive negative binomial models adjusted for spatial trends, access to treatment, and health district size, where a 4.3% increase in deforestation was associated with a 48% increase in the incidence of malaria 12 .…”
mentioning
confidence: 93%
“…In frontier settlements, children (highly susceptible), if not adults, will perpetuate and amplify malarial infection. Disease fronts can establish: 99 per cent of Brazil's malaria now occurs in the Amazon basin (Chaves et al 2018).…”
Section: Ending Epidemics and Controlling Communicable Diseasesmentioning
confidence: 99%